PELATIHAN MEDIA PEMBELAJARAN INTERAKTIF MATEMATIKA BERBASIS ANDROID BAGI GURU DAN SISWA SD ADVENT ABEPURA PAPUA - Wororomi, Jonathan K.; Tandiangnga, Tiku; Sampebua, Mingsep Rante (JURNAL PENGABDIAN PAPUA, 2024)
Children The problem with the learning system at Abepura Adventist Elementary School is that students feel bored with the teacher-centered learning process and they are not active and interested in learning mathematics. The aim of the Uncen PNBP service in 2023 is training in Android-based interactive mathematics learning media for teachers and students at Abepura Adventist Elementary School which can support the teaching and learning process. The methods of service activities are lectures, discussions, questions and answers, demonstrations and practice in using Android math applications. The results achieved from the Uncen PNBP service are that teachers and students can use the Android math application as an interactive learning medium that can increase knowledge, skills and innovation in information and communication technology-based learning models.